THE RELATIONSHİP BETWEEN HUMAN RESOURCES SELECTION PROCESS WITH THE OF HUMAN RESOURCES QUALIFICATION: THE SAMPLE OF PROVINCE ŞANLIURFA - Ferit KÜÇÜK (Fırat University, 2019)
The aim of this study; to determine the relationship between with the selection process of human resources and the quality of human resources at private hospitals in Şanlıurfa. It has been identified as a sample of private hospitals with operations in Sanliurfa. six private hospitals survey method was applied to the human resources manager. It was taken to determine the relationship between businesses and human resource selection process, quality of human resources. By SPSS 16 software evaluation of the data, the frequency, and chi-square statistical analyzes were performed. The nature of work and labor plans, with job analysis and job descriptions is determined that there is a relationship between the quality of human resource it is determined that there is a relationship. among the qualifications required to work with business. ns